PENGARUH PENGGUNAAN KAPUR BAKAR DAN KAPUR GILING (MILL) TERHADAP KUAT TEKAN SPESI - Endaryanta Endaryanta (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTBurned and raw limestone powder is a kind of binder that has been widelyused in traditional construction of masonry and clay brick wall. Nowadays,limestone powder also widely used in many construction projects as a portlandcement admixture. This research is designed to examine the effects of burnedand raw limestone powder on the compressive strength of mortar.This research has been done with experimental method using variouscomposition in mortar mix design. The compositions that used in this researchare 1:1/4:3, 1:3/4:3, 1:1:3 and 1:2:3 of portland cement, limestone powder andsand, with six standard cubes for each average of mortar compressive strength,that have been tested in the Laboratory of Building Material, Department of CivilEngineering and Planning Education, Faculty of Engineering in State Universityof Yogyakarta.Test results indicate that (a) average of mortar compressive strength using1:1/4:3 composition of portland cement, limestone powder and sand is 24,79MPa for burned limestone powder and 16,3 MPa for raw limestone powder, (b)average of mortar compressive strength using 1:3/4:3 composition of portlandcement, limestone powder and sand is 14,14 MPa for burned limestone powderand 13,28 MPa for raw limestone powder, (c) average of mortar compressivestrength using 1:1:3 composition of portland cement, limestone powder and sandis 12,28 MPa forburned limestone powder and 7,78 MPa for raw limestonepowder, (d) average of mortar compressive strength using 1:2:3 composition ofportland cement, limestone powder and sand is 8,56 MPa for burned limestonepowder and 7,18 MPa for raw limestone powder, (e) There is a significantdifference of mortar compressive strength using burned limestone powder andraw limestone powder, (f) the use of burned limestone powder as portland cementadmixture is better than raw limestone powder that indicated from the result ofcompressive strength tests.Keywords: nlortar, conzpressive strength, lilnestone po~vder.